Coordination behavior, structural, statistical and theoretical investigation of biologically active metal-based isatin compounds - Sumrra, Sajjad Hussain; Mushtaq, Fazila; Ahmad, Fayyaz; Hussain, Riaz; Zafar, Wardha; Imran, Muhammad; Zafar, Muhammad Naveed (Chemical papers, 2022)
Isatin-core-containing ligands were synthesized by reacting an equimolar ratio of isatin with ethanolamine and anthranilic acid, respectively. The ligands were characterized by using FT‐IR, UV–Vis, 1 H-NMR, ESIMS and elemental analysis. The synthesized ligands were further complexed with transition metal ions in a 1:2 molar ratio. Metal complexes were also characterized by physical, analytical and spectral methods in addition to molar conductance and magnetic moment measurements. The DFT calculations at B3LYP/6–311 +  + G(d,p) level were accomplished for comparative study of isatin-based compounds. A good agreement among experimental UV–Vis, FT-IR and corresponding DFT results was found, which confirmed the purity of the studied compounds. The antimicrobial profile of all the compounds was evaluated by testing their antibacterial activity against two species of Gram-positive bacteria ( Staphylococcus aureus, Streptococcus pyogenes ) and two species of Gram-negative bacteria ( Pseudomonas syringae, Escherichia coli ) and antifungal activity against three species of fungi ( Aspergillus niger, Rhizopus stolonifer and Trichoderma spirale ) using the disk diffusion method. Moreover, the compounds were also investigated for antioxidant activity using phosphomolybdate and DPPH assays. The ligands revealed moderate activity against targets, which increased further upon complexation with different metal ions due to the chelation process. In addition, ANOVA and Tukey test for the experimental results of biological activities for all the prepared compounds supported the significant difference in all preclinical treatments’ performance. The results showed that the isatin metal-based compounds are potent for being active as antimicrobial and antioxidant prototypes. Graphical abstract